Containment control of heterogeneous multi-agent systems subject to Markovian randomly switching topologies and unbounded delays - Haihua Guo; Gang Feng; Cong Bi (Journal of Automation and Intelligence)
This paper addresses the problem of containment control for heterogeneous multi-agent systems subject to Markovian randomly switching topologies and unbounded communication delays. The objective is to design a distributed control strategy that ensures the output of each follower converges to the convex hull formed by the outputs of a group of leaders in mean square sense. A novel distributed observer is proposed by tackling both Markovian randomly switching topologies and unbounded delays. Then, a distributed state feedback controller and a distributed output feedback controller are developed based on the distributed observer, respectively. Finally, simulation results are provided to demonstrate the effectiveness of the proposed controllers.